A zoning model for seismic hazard analysis of Finland and adjacent areas : A fusion of seismological and geological data - Mäntyniemi, Päivi; Fülöp, Ludovic; Oinonen, Kati; Junno, Niina; Kosonen, Emilia; Korja, Annakaisa (Elsevier B.V., 2025)
We present a new seismic zoning model for the territory of Finland and adjacent areas in northern Europe for the purpose of seismic hazard mapping. The target region, mostly situated in the stable continental region of the Fennoscandian Shield, exhibits predominantly earthquakes below moment magnitude 3.0. We have delineated area seismic source zones by fusing seismological, geological, and geophysical data, and tectonic boundaries. The approach is warranted to find sufficient argumentation on the zoning due to the poor to non-existent seismicity data in the eastern and southeastern part of our target region. We have addressed the subjectivity included in delineation of zone boundaries by combining the preliminary delineations of four expert groups into a model with three levels of details: macro-, meso- and microlevel. We compare the new microlevel zoning with the regional zoning models of 2015 and 2016 and all the three zonings with the respective zonings of the 2020 European Seismic Hazard Model. We argue that the new zoning model SZ2025FI provides a sufficient basis for seismic hazard mapping on national and regional scales, as well as European and global mapping initiatives. We present a new seismic zoning model for the territory of Finland and adjacent areas in northern Europe for the purpose of seismic hazard mapping. The target region, mostly situated in the stable continental region of the Fennoscandian Shield, exhibits predominantly earthquakes below moment magnitude 3.0. We have delineated area seismic source zones by fusing seismological, geological, and geophysical data, and tectonic boundaries. The approach is warranted to find sufficient argumentation on the zoning due to the poor to non-existent seismicity data in the eastern and southeastern part of our target region. We have addressed the subjectivity included in delineation of zone boundaries by combining the preliminary delineations of four expert groups into a model with three levels of details: macro-, meso- and microlevel. We compare the ...